PENGGUNAAN MEDIA KARTU GAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DI KELAS II SDN 096 SARIJADI SELATAN KECAMATAN SUKAJADI KOTA BANDUNG - Dede Wiwin Rahmadini; Effy Mulyasari; Eva Riyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is undermined by the fact that the level of students' reading ability in class 2B of SDN 096 Sarijadi Selatan Bandung is still low, especially for beginning reading. This is due to various reasons, including the preliminary reading carried out by the class 2B teacher, which is less attractive to students and the result is only 10% of the number of students who are able to follow the lesson well. One way that can be used is to apply the use of picture card media. Picture cards can make it easier for students to read words which then become sentences. The purpose of this study was to improve the beginning reading skills of class 2B students at SDN 096 South Sarijadi, Sukajadi District, Bandung. This type of research is classroom action research. The design in this study uses the Kemmis and Tagart models which have four stages in conducting classroom action research, namely planning, action, observation and reflection and consisting of two cycles. Data collection is done by observation, interviews and tests. Based on the results of data analysis it is known that the use of picture card media can improve the beginning reading ability of class 2B students at SDN 096 Sarijadi Selatan Bandung. The class average value in the first cycle was 60.4 and increased to 75.6 in the second cycle. Based on the findings in this study, it was concluded that the application of picture card media in learning has a considerable impact on the beginning reading ability of grade 2B students at SDN 096 Sarijadi Selatan.